Evaluasi User Experience terhadap Minat Penggunaan E-Money di Indonesia - Dina Fitria Murad; Silvia Ayunda Murad; Siti Maryam; Riyan Leandros; Andika Hairuman (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2026)
The development of digital payment systems has driven the increasing use of electronic money (e-money) in Indonesia. However, the level of adoption and sustainability of its use are greatly influenced by user experience. This study aims to analyze the influence of user experience on the intention to use e-money through a quantitative approach with a survey method of 100 e-money users. Data were analyzed using descriptive statistics, Cronbach's Alpha reliability tests, and simple linear regression. The results showed that the user experience and intention to use instruments had very good reliability with Cronbach's Alpha values of 0.879 and 0.886, respectively. Regression analysis showed that user experience had a positive and significant effect on the intention to use e-money (β = 1.399; p < 0.001), with a coefficient of determination (R²) of 0.684. These findings indicate that user experience is an important factor in explaining variations in the intention to use e-money. Aspects of ease of use, convenience, and user satisfaction have been shown to play a role in increasing the adoption and sustainability of e-money use. The research results are expected to be a reference for application developers and stakeholders in improving the quality of e-money services.